Active filter design to reduce the harmonics level generated by non linear load / Shahrul Azli Md Shah - Md Shah, Shahrul Azli (2005)
Nonlinear load is one of the common sources of harmonic. The harmonic content that exceeds the IEEE 519 limits will harmful the overall system connected to the nonlinear load. Active filter is one of the alternative approaches to reduce the harmonics content. Therefore, proper active filter (AF) design is required to reduce the harmonics content produced by non linear load. For that purpose this thesis presents the development of single phase active filter simulation model using digital simulation software. The model is simulated with rectifier and semi-converter located at the load side. Without installing the active filter, these loads caused the total harmonic distortion (THD) goes high. However, with the aids of active filter simulation model, the results show some reduction in harmonic level Active filters are used to reduce harmonics generated by non-linear loads, such as, for example, rectifiers of the electrical drive. Distortion of sinusoidal voltage and current waveforms caused by harmonics is one of the major power quality concerns. Nonlinear load such as traditional diode / thyristor rectifiers with capacitive and inductive load generate harmonic and reactive current, which lead to poor power factor, low energy efficiency and harmful disturbance to the other appliances. The harmonic pollution can be reflected by harmonic current components, which bring about more serious problem than harmonic voltage components in some cases [I].